(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
An emerging subcategory of ad hoc networks known as "vehicular ad hoc networks" (or "VANETs"), this type of network allows cars to communicate and share data with one another in a manner that is decentralized. The vulnerability of the VANET stems from the fact that communication between vehicles takes place in an open environment. Authentication techniques are an essential component of VANETs since they enable secure communication between vehicles. The implementation of cluster-based authentication protocols is a typical strategy that is utilized for the protection of VANETs. As part of our research, we deliver a trustworthy authentication system that is built on clusters and is intended for usage in VANETs. Our strategy makes use of public-key cryptography to protect against forgeries. This is accomplished by placing the onus of verifying the authenticity of cars on the cluster head. We show that our protocol is resistant to a wide range of attacks and that it can permit authentication in VANETs that is both quick and reliable.